Storage-efficient method for generating contours focusing on roundness. Issue 2 (1st February 2016) - Goto, Hiroyuki; Shimakawa, Yoichi
Abstract : A storage-efficient contour generation method, focusing on planar contours, is developed. Given cartographic elevations on a rectangular lattice, a continuous bivariate function, z  =  f ( x, y ), is determined by interpolating the elevation values. Then, we focus on a contour determined by z  = constant. The contour curve is partitioned into multiple sections, each of which is exactly or approximately round. Three curvature types are introduced to evaluate the roundness of each section. The area and perimeter of the contour are computed by one-dimensional line integration using Green's theorem. If the contour is open, it is divided into two curves starting from the same initial point, with the control points advancing in opposite directions. Two types of numerical experiments are performed to validate the effectiveness of the proposed method. One experiment uses an analytically defined elevation function and investigates the number of control points and computation time for a resulting computation error. The second experiment uses actual digital elevation model data of an isolated island in Japan and compares the proposed method with existing ones. Because the algorithm does not require lattice subdivision and the number of control points is drastically reduced, the proposed method is storage efficient.